1997
DOI: 10.1023/a:1018514415073
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Brain lesions, even of the most subtle type, are accompanied by the activation of microglia, the main immune cells of the brain. Microglial cells dramatically increase in number through proliferation and adhere to the injured neurons, where they displace the synaptic input. After proliferation, microglia gradually migrate into the nearby parenchyma and appear to decrease in number. Here we examined the possible involvement of apoptosis in the regulation of the microglial cell number using Terminal transferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this paradigm PDE4B was constitutively localized to the nucleus. Although cytokine stimulation of microglia often leads to their apoptosis (Jones et al, 1997), it is yet to be determined what is the role of the transient nuclear translocation of PDE4B from the cytoplasm in activated microglia in the current study and whether such translocation involves either a cyclic AMP hydrolytic function of PDE4B in the nucleus or whether PDE4B participates as a scaffolding molecule with other signaling intermediaries. Through the use of PredictNLS we have shown that PDE4B2 may contain a putative [DE]RxKKKK NLS sequence, which was highly conserved among species.…”
Section: Discussionmentioning
confidence: 89%
“…In this paradigm PDE4B was constitutively localized to the nucleus. Although cytokine stimulation of microglia often leads to their apoptosis (Jones et al, 1997), it is yet to be determined what is the role of the transient nuclear translocation of PDE4B from the cytoplasm in activated microglia in the current study and whether such translocation involves either a cyclic AMP hydrolytic function of PDE4B in the nucleus or whether PDE4B participates as a scaffolding molecule with other signaling intermediaries. Through the use of PredictNLS we have shown that PDE4B2 may contain a putative [DE]RxKKKK NLS sequence, which was highly conserved among species.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, it has recently been shown that microglia are able to cross-present exogenous antigens on MHC I to CD8+ T cells [61]. In the course of recovery from injury, activated microglia can be eliminated by apoptosis [54,62]. Not only neurons, but also astrocytes can be critical for microglial activation, e.g.…”
Section: Mechanism Of Microglial Activationmentioning
confidence: 99%
“…LCMV infection between males and females, removal of endogenous androgens in males via orchidectomy decreased the number of CD45 int cells compared to sham-operated males, and addition of exogenous androgens to female mice via DHT pellet implantation increased the number of CD45 int cells compared to control females. Microglia are able to undergo proliferation and apoptosis in response to various stimuli (Jones et al, 1997; Remington et al, 2007; Wirenfeldt et al, 2007), but little is known about the effects of sex hormones on these processes in microglia. Possible roles of physiologic levels of estrogens on microglial survival/proliferation and the balance of estrogens’ effects with the effects of androgens must also be considered.…”
Section: Discussionmentioning
confidence: 99%